2018
DOI: 10.1002/em.22208
|View full text |Cite
|
Sign up to set email alerts
|

Association of Interleukin‐1 beta and tumor necrosis factor‐alpha genetic polymorphisms with gastric cancer in India

Abstract: Interleukin 1 beta (IL-1β) and Tumor necrosis factor alpha (TNF-α) are key inflammatory cytokines whose polymorphisms have been correlated with increased susceptibility to gastric cancer (GC). Since geographical and racial differences exist in cancer rates, our study was aimed to evaluate the first possible association of polymorphisms in these genes with GC risk in West Bengal, India. Polymorphisms in IL-1β and TNF-α genes were genotyped in 120 GC patients and 135 healthy individuals. Combined effect of the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 70 publications
(87 reference statements)
1
9
0
1
Order By: Relevance
“…It suggested that IL-6 SNPs are very useful prognostic biomarkers in clinical usage and could be truly specific in prognosis of a particular cancer type (18). These results are completely consistent with other investigations (46)(47)(48). IL-1α and IL-1β, two members of IL-1, have a common receptor with shared SNPs (IL-1α-889C>T and IL-1β-3737C>T) (49).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…It suggested that IL-6 SNPs are very useful prognostic biomarkers in clinical usage and could be truly specific in prognosis of a particular cancer type (18). These results are completely consistent with other investigations (46)(47)(48). IL-1α and IL-1β, two members of IL-1, have a common receptor with shared SNPs (IL-1α-889C>T and IL-1β-3737C>T) (49).…”
Section: Discussionsupporting
confidence: 81%
“…Recently, Sultana et al, (2018) (48) indicate that the C allele of IL-1α-889 is higher in MM patients than in controls. Similarly, Ziakas et al, (2013) (50) show that the G allele of IL-1β-1464G>C was significantly associated with MM in an Asian population.…”
Section: Discussionmentioning
confidence: 98%
“…Lastly, intrinsic mutations and polymorphisms in IL-1 genes have been implicated as well in many cancer types as reviewed by Khazim et al [ 79 ], though results from studies are sometimes conflicting, and the association is not always clear. Single and IL-1 gene-cluster polymorphisms have been suggested to be associated with cancers such as cervical [ 80 ] and ovarian cancer [ 81 ], MM [ 82 ], esophageal [ 83 ], colorectal cancer (CRC) [ 84 ], NSCLC [ 85 ], pancreatic cancer [ 86 ], prostate cancer [ 87 ], and gastric cancer [ 88 90 ].…”
Section: Il-1 Dysregulation and Its Contribution To Cancer And Tumorimentioning
confidence: 99%
“…Moreover, many associations of TNF_rs1800630 * A with diseases have been reported. Those of enhanced susceptibility to cancer seem to indicate that reduced TNF levels increase the chance of inappropriate cell proliferation, due to insufficient signaling for apoptosis/necroptosis [e.g., hepatocellular carcinoma (43), non-Hodgkin lymphoma (44, 45), gastric cancer (46), and colon cancer (47)]. On the other hand, the same allele was associated with progression to and severity of infections, as for severe malaria, including cerebral malaria (48, 49), HPV-associated oral squamous carcinoma (50), HBV chronification (51), as well as with chronic disorders, which may rely on insufficient immunological response to different kinds of aggressors [steroid-induced osteonecrosis of the femoral head (52), progression of acute pancreatitis to systemic inflammation and multi-organ dysfunction syndrome (53), chronic periodontitis (54), and cardiovascular heart disease (55)].…”
Section: Discussionmentioning
confidence: 99%